Qualitative Methods Module 20 - Bailey, Kathleen (TRAILS: Teaching Resources and Innovations Library for Sociology, 2010)
The resurgence of gang activities in the 1980s and 1990s has prompted manybooks and articles about the subject of gangs. According to the literature there are moregangs than in past years, more youth in those gangs, and more communities experiencinggang problems (National Youth Gang Center, 1997). Although students are interested inreading and understanding the qualitative issues surrounding gangs (poverty, identity,peer group involvement, family relationships, power and safety issues, culture, etc,) fewstudents truly understand the depth and breadth of the struggle. Generally, fewopportunities arise in their world to challenge their understanding of why youth joingangs. They often have limited ideas of how it feels to be denied equal opportunity, to bein a different place of human standard, justice, mercy, rectitude, and fair play. Accordingto Kegan (1982, pg. 148) "…what they need most of all is a kind of intimate participation in their personal experience of evolution..."